Insight, duration of untreated psychosis and attachment in first-episode psychosis: prospective study of psychiatric recovery over 12-month follow-up. (July 2014) - Gumley, A. I.; Schwannauer, M.; Macbeth, A.; Fisher, R.; Clark, S.; Rattrie, L.; Fraser, G.; McCabe, R.; Blair, A.; Davidson, K.; Birchwood, M.
Abstract : Background: Increasing evidence shows attachment security influences symptom expression and adaptation in people diagnosed with schizophrenia and other psychoses. Aims: To describe the distribution of secure and insecure attachment in a cohort of individuals with first-episode psychosis, and to explore the relationship between attachment security and recovery from positive and negative symptoms in the first 12 months. Method: The study was a prospective 12-month cohort study. The role of attachment, duration of untreated psychosis (DUP), baseline symptoms and insight in predicting and mediating recovery from symptoms was investigated using multiple regression analysis and path analysis. Results: Of the 79 participants, 54 completed the Adult Attachment Interview (AAI): 37 (68.5%) were classified as insecure, of which 26 (48.1%) were insecure/dismissing and 11 (20.4%) insecure preoccupied. Both DUP and insight predicted recovery from positive symptoms at 12 months. Attachment security, DUP and insight predicted recovery from negative symptoms at 12 months. Conclusions: Attachment is an important construct contributing to understanding and development of interventions promoting recovery following first-episode psychosis.